In vitro transcription and translation of simian rotavirus SA11 gene products. - Mason, B B (1980)
Rotavirus gene products were examined, with the simian rotavirus SA11 as a model. The endogenous viral RNA-dependent RNA polymerase associated with single-shelled virus particles or with activated double-shelled particles was used to synthesize viral RNA transcripts. Sedimentation velocity sucrose gradient analysis of the RNA transcripts revealed four peaks at 9S, 12S, 14S, and 18S, whereas agarose gel electrophoresis under partially denaturing conditions revealed eight groups of RNA species ranging in molecular weight from 2 x 10(5) to 1.2 x 10(6). The transcripts synthesized in vitro were active in an mRNA-dependent cell-free translation system derived from rabbit reticulocytes. The transcripts directed the synthesis of 11 polypeptides that had molecular weights ranging from 125,000 to 20,000 when analyzed by electrophoresis in sodium dodecyl sulfate-polyacrylamide gels. The products of in vitro translation were compared with polypeptides from purified virus and those synthesized in infected cells. Several of the polypeptides synthesized in vitro were designated as structural polypeptides by comparing the molecular weights determined by polyacrylamide gel electrophoresis analysis or by precipitation with hyperimmune serum prepared against purified virus. Three of the viral structural polypeptides (VP4, -5, and -5a) were not synthesized in vitro as primary gene products, demonstrating that processing must occur for the production of some structural polypeptides. Other in vitro-synthesized polypeptides were tentatively identified as either precursors to the viral glycoproteins or nonstructural polypeptides.